N-(2-Methoxyphenyl)phthalimide - Ariffin, Azhar; Ng, S.W.; Sim, Y.L.; Khan, M.N. (International Union of Crystallography, 2009)
The phthalimide fused-ring system and the phenylene ring in the title compound, C15H11NO3, are inclined at an angle of 54.2 (1)degrees.